Case Report: Novel Anchoring Technique and Surgical Nuances for Trigeminal Ganglion Stimulation in the Treatment of Post-Herpetic Trigeminal Neuropathic Facial Pain - Gupta, Kunal (Frontiers in Pain Research, 2022)
Introduction Trigeminal ganglion stimulation is a neuromodulatory surgical procedure utilized to treat trigeminal neuropathic pain. Wider adoption by surgical practitioners is currently limited by lead migration from the trigeminal ganglion, which can result in loss of therapy and cannot be rectified without repeat surgery. We describe a novel surgical modification that successfully anchors the trigeminal ganglion electrode long-term. Objective To describe a novel surgical technique for anchoring of trigeminal ganglion stimulation electrodes Methods Surgical technique An electrode is inserted percutaneously through the foramen ovale into Meckel’s cave, adjacent to the trigeminal ganglion. The lead is anchored using modification of an existing anchoring device, inserted into the buccal incision. The lead is connected to a generator for therapeutic stimulation. Results Case Report A 74-year-old male with post-herpetic trigeminal neuropathic pain, who had failed prior surgical therapies, underwent trigeminal ganglion stimulation. The trial lead was anchored using standard techniques and migrated outward within 7-days. The permanent lead was anchored using the described novel technique and remained in position without clinically significant outward migration until last follow-up at 8-months. Conclusion Trigeminal ganglion stimulation is an effective therapeutic option for trigeminal neuropathic pain. The novel surgical adaptation described prevents outward migration of the lead and stable lead placement long-term.